Social Signaling and Urea Excretion in the Gulf Toadfish, Opsnus beta - Fulton, Jeremy (Université d'Ottawa / University of Ottawa, 2013)
The gulf toadfish (Opsanus beta) is a member of a group of teleosts that have retained their ornithine urea cycle (OUC) allowing them to excrete nitrogenous waste in the form of urea (ureotely). Urea-N for the entire day is excreted in 1-2 quick pulsing events (1-3 h). This study evaluated the hypothesis that urea-N pulsing events in gulf toadfish can be triggered by social signals from conspecifics via a specific waterborne messenger. Using a crowding protocol, we found that pre-conditioned seawater induced a secondary urea pulsing event in naïve conspecifics. Furthermore, it was revealed that other factors such as signal concentration and donor body mass relay information to recipients as well. Fractionation of pre-conditioned seawater was carried out to narrow possible signal candidates and the aqueous portion was found to contain the active molecule. Ammonia was found to be an important factor controlling the response of toadfish to pre-conditioned seawater.
Keywords: Opsanus beta; Social signaling; Ureotely; Toadfish